Street art, public city: law, crime and the urban imagination - Young, Alison (A GlassHouse book, 2014)
"This book investigates street art and graffiti as cultural practices at the borders of legality and illegality. Cities are engaged in a continual process of cultural production through which their self-image is developed and refined; a process that is sometimes legal -- as with architecture, statuary, signage, advertising, and public art -- and sometimes not -- with practices such as billposting, graffiti and street art. Alternately (and sometimes simultaneously) considered criminal, gentrifying, or commercial, street art exists and operates on the boundaries between the legal and illegal, and between art, crime, and culture. Given its capacity to generate discussion and polarise opinion, street art is a cultural practice that can inform us about the nature of urban life and the limits of public space. Street Art, Public City: Crime and the Urban Imagination draws upon fifteen years of research to examines the ways in which street art has become as integral part of cities' cultural identities. It will be of interest to readers in the fields of street art and graffiti specifically, but also to those interested in issues relating to cities and urban space, legal geography, cultural criminology as well as cultural studies and art more generally. "--